Effects of temperature on the stability of Rickettsia tsutsugamushi and gamma-irradiated scrub typhus immunogens. - Eisenberg, G H (1978)
Unirradiated Rickettsia tsutsugamushi and a component of gamma-irradiated Karp immunogen required for homologous immunity were more stable than the immunogen component that elicited heterologous (Kato strain) protection.